Epidemiological analysis of Leishmaniasis prevalence in Pakistan during 2016-2023 - R. Uppal; U. Saeed; M. E. Khattak; A. A. Khan; M. R. Uppal; Z. Z. Piracha; M. N. Khan; D. Shaikh; U. Tariq; A. R. Mahmood; S. S. Ali; B. Muhammad; et al. (Brazilian Journal of Biology)
Abstract Leishmaniasis, caused by the Leishmania parasite, remains a persistent public health challenge in Pakistan. Despite control efforts, the disease prevalence continues to rise, particularly among pediatric populations. Understanding prevalence patterns and transmission dynamics is critical for effective control strategies. This study aims to analyze leishmaniasis prevalence data from January 2016 to July 2023 in Pakistan. Specific objectives include assessing temporal trends, demographic patterns, and geographical hotspots of transmission, while emphasizing the need for enhanced surveillance and research for targeted interventions. Retrospective analysis was conducted on leishmaniasis prevalence data collected from multiple healthcare facilities across Pakistan. Data included results from diagnostic tests on suspected cases, encompassing both pediatric and adult patients. Descriptive statistical analysis was employed to evaluate prevalence rates, demographic characteristics, and geographical distribution of positive cases. Analysis revealed an increasing trend in leishmaniasis prevalence over the study period. Initially, from 2016 to 2020, a positivity rate of 27% was observed exclusively among pediatric patients in Islamabad, with no adult cases. Subsequently, from 2017 to 2022, the positivity rate increased to 42%, affecting both pediatric and adult populations in Islamabad, Rawalpindi, and Swat. Notably, between July 2022 and July 2023, the positivity rate surged to 56%, primarily impacting adult males in the identified hotspots. The study provides evidence of rising leishmaniasis prevalence in Pakistan, particularly among pediatric patients. Identified hotspots suggest localized transmission, warranting targeted interventions. Enhanced surveillance and research efforts are crucial for understanding disease dynamics and implementing effective control measures. Priority should be given to vulnerable populations and high-burden regions to mitigate leishmaniasis impact in Pakistan.